2001
DOI: 10.1159/000054680
|View full text |Cite
|
Sign up to set email alerts
|

A Role of Ghrelin in Neuroendocrine and Behavioral Responses to Stress in Mice

Abstract: Ghrelin, an endogenous ligand of the growth hormone secretagogue receptor, was recently identified in the rat stomach. Previous studies have shown that ghrelin potently increases growth hormone release and food intake. We examined the effects of the gastric peptide ghrelin on anxiety-like behavior in association with the hypothalamic-pituitary-adrenal axis in mice. Both intra-third cerebroventricular and intraperitoneal administration of ghrelin potently and significantly induced anxiogenic activities in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
272
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(294 citation statements)
references
References 15 publications
10
272
2
6
Order By: Relevance
“…2a). This finding is consistent with previous studies that have demonstrated increases in gastric ghrelin mRNA or total plasma ghrelin after acute stress 5,6 .…”
Section: Online)supporting
confidence: 94%
“…2a). This finding is consistent with previous studies that have demonstrated increases in gastric ghrelin mRNA or total plasma ghrelin after acute stress 5,6 .…”
Section: Online)supporting
confidence: 94%
“…Ghrelin stimulates the HPA axis via stimulation of CRH release from the hypothalamus. Blockade of CRF receptors has been shown to attenuate ghrelin-induced anxiogenesis in the elevated plus maze test (Asakawa et al, 2001a), and injection of astressin (CRF2 receptor antagonist) attenuated ghrelin-induced plasma corticosterone increase in neonatal chicks (Saito et al, 2005). We have demonstrated that CRF, like ethanol, augments GABAergic transmission, and that ethanol dependence heightens the sensitivity to CRF and CRF 1 antagonists in CeA (Roberto et al, 2010).…”
Section: Discussionmentioning
confidence: 69%
“…In mice, peripheral and central administration of ghrelin reduced the total number of entries and total time spent in the open arms in an elevated plus maze test (Asakawa et al, 2001a). Furthermore, starvation stress increased ghrelin gene expression (Asakawa et al, 2001b) and tail pinch stress significantly increased ghrelin mRNA expression (Asakawa et al, 2001a).…”
Section: Discussionmentioning
confidence: 97%
“…Ghrelin levels are reported to be decreased in obesity (13) and increase after diet-induced weight loss (14). Preliminary data in rodents suggest that ghrelin can also affect neuroendocrine and behavioral responses to stress (15).…”
mentioning
confidence: 99%